Two Unities of Consciousness. (27th December 2010) - Schechter, Elizabeth
<x xml:space="preserve">Abstract</x> Abstract: This paper argues for a distinction between possession of a unified consciousness and possession of a single stream of consciousness. Although the distinction has widespread applicability in discussions of the structure of consciousness and of pathologies of conscious experience, I will illustrate its importance primarily using the debate about consciousness in split‐brain subjects, suggesting that those who have argued that split‐brain subjects have two streams of consciousness apiece and those who have argued that they have a unified consciousness may both be right.